Potensi Kerjasama Regional Usaha Mikro Kecil Menengah (Umkm) Berbasis Komoditas Pertanian Di Kabupaten Simalungun - Pranata Silalahi, Puji Abraham; Surjono, Surjono; Wijayanti, Wawargita Permata (Fakultas Teknik, Universitas Brawijaya, 2016)
MSMEs takes an important role to develop local potential and provides jobs so that the poverty can be reduced. But nowdays, regional development policy doesn’t show the importance of MSMEs to increace economy in small and medium scale. Regional development policy in Simalungun Regency takes a program to empower community through the agroindustry. That policy needs to support with the sustainability of the commodities availability. So that MSMEs can be grow up. Simalungun Regency has local potential with the number of MSMEs and agriculture commodities that can be expanded. This study aims to determine the commodities that has potential to do regional cooperation pattern in each sub-district in Simalungun Regency. This study using some method, location quotient (LQ) analysis was used to identify the commodities base, and LISA analysis was used to determine the comodities and the sub-district location that have potential to do a regional cooperation. The result of this study shows that the agricultural commodities that have potential to do a regional cooperation pattern are corn, soy, peanut, cassava, jackfruit, fish, carrot, coffee, cacao, and sugar palm.Keywords: MSMEs, agricultural-commodities, poverty, LISA.